562 Development of a group/organization-focused diagnostic sheet for occupational health nursing. (24th April 2018) - Ito, M; Akimoto, F; Hara, K; Masuzawa, K; Ito, M; Nakamur, H; Yanai, M; Murakami, K; Nagano, A; Seto, M; Yamaguchi, Y; Yoshida, R; et al.
Abstract : Background: Group/organization-focused quality nursing practices are expected of occupational health nurses, as the maintenance and promotion of the health of workers cannot be achieved without the wellbeing of the group/organisation in which they work. Purpose: In this research we developed a new sheet integrating diagnosis, outcome, and organisational support, in which the entire nursing process should be covered. Methods: Cases involving major workplace health issues were subject to discussion among members consisting of 3 nursing diagnosis researchers and 9 occupational health nursing specialists. During the discussion, Herdman Nursing Process, NANDA-I Nursing Diagnosis, and NIC-categorised Nursing Intervention were used for references. Supervision by nursing diagnosis research specialists, advice from the special committee members of JAOHN, and opinions of nationwide working-group members were obtained. Results: The findings of the discussions, followed by qualitative analyses, were summarised for use in the sheet development. Diagnosis were made, definitions were clarified, and the nursing outcomes were identified based on the related factors, risk factors, and defining characteristics. After clarifying the challenges faced by the group/organisation, a diagnosis sheet was developed (figure 1). Discussion: The availability of this new sheet should encourage development of more systematised nursing diagnosis in occupational nursing, which is considered to be an urgent issue in Japan.